Ovid and the Renaissance body - Stanivukovic, Goran V. (University of Toronto Press, 2001)
This collection of original essays uses contemporary theory to examine Renaissance writers' reworking of Ovid's texts in order to analyze the strategies in the construction of the early modern discourses of gender, sexuality, and writing.